Blood substitution therapy rescues the brain of mice from ischemic damage - Xuefang Ren (Nature Portfolio, 2020)
Acute stroke causes complex, pathological, and systemic responses which remain challenging to treat. Here, the authors show that substituting the blood of stroke model mice with whole-blood from naive healthy donor mice reduces infarct volume and improves neurological deficits.